Implementation of environmental learning in the NSSC biology curriculum component: a case study of Namibia - Tshiningayamwe, Sirkka Alina Nambashusan (Rhodes University, Faculty of Education, Department of Education, 2012)
In the context of ecological crisis and environmental deterioration, teaching about environmental issues and the preservation of the world's environment has become increasingly important across the globe (Chi-chung Ko & Chi-kin Lee, 2003). Of the various subjects taught in secondary schools, Science is often perceived as one that can make a significant contribution to environmental education. It is in this light that the study has looked at how Grade 11 and 12 Biology teachers in the Namibian context implement Environmental Learning (EL). This study was constituted as a case study of two schools in Windhoek, in the Khomas region. The study investigated the implementation of EL in the Biology curriculum focusing on the constraints and enabling factors influencing the implementation. This study employed qualitative methods, specifically semi-structured interviews, classroom observations and document analysis in its investigation of EL implementation. Purposive sampling was done and piloting of interview and observation schedules was used to refine the schedules. Ethical issues were taken into consideration throughout the study. The key findings from the study are as follows: - Teachers' knowledge and interest in environmental education influence how teachers facilitate EL; - There is a mismatch between EL theories and practice; - Teaching of EL is mainly informed by the syllabus and not other curriculum documents, - Current assessment policy and practice impact on EL; and - Possibilities exist for improving EL in Namibia's Biology curriculum. These key findings have been used to make recommendations for the study which are as follows: - Strengthen the subject content and interest of teachers; - There should be a match between EL theories and practice; - Reorient curriculum documents and other learning support materials used for EL; - Change in assessment approaches; and - Translate constraints of EL into enablers. The study concludes by calling for further research into EL pedagogies. This can be used to improve EL implementation in the region where the study was situated.
Keywords: Environmental education -- Namibia -- Case studies; Environmental education -- Study and teaching (Secondary) -- Namibia -- Case studies; Environmental education -- Evaluation -- Namibia -- Case studies; Biology -- Study and teaching (Secondary) -- Namibia -- Case studies; Biology -- Curricula